Politik Identitas dan Multikulturalisme : The Gods Must be Crazy II (1989) - yati, Mulyati; Hellen Permatasari; Dini Otafiana; Tini Haryani; Aswandi; Alif Farhan Habibie; Marlina; Kustiawan (STISIP Widyapuri Mandiri Sukabumi, 2024)
The aim of this research is to find out what happens to identity politics and multiculturalism in the film